Traditional Marriages in Rural Balochistan: The Voice of Baloch Women - Umer, Shumaila; Othman, Zaheruddin; Hassan, Kalthum (2017)
Marriage is an essential and universal socially accepted institution that indicates the pattern of civilised society.It is the bond between two individuals to form a family.It is recommended by many religions for the sake of eradicating the social evils of society.However, the traditional marriages which occur on the basis of a violation of individual rights, give air to hostile social situations.This study aimed to explore the views of Baloch women regarding the consequences of traditional marriages on their lives.The study was undertaken in 4 villages of Punjpahee subtehsil of Balochistan, Pakistan, focused on 20 women informants.The data were collected through focused group discussion.The study sensed traditional marriages are due to the deeply rooted socio-cultural norms, illiteracy, and preference of the male child, therefore these traditions put women in a disadvantaged position.It is highly recommended that NGOs and GOs play a better role in the awareness of the parents and implementation of the laws regarding the rights of women so that they can lead better-privileged lives, with the help of religious scholars and media.